SANTRI Application Supports Digital Healthcare Services at RSUD Sidoarjo: Aplikasi SANTRI Mendukung Layanan Kesehatan Digital di Rumah Sakit Umum Daerah Sidoarjo - Putry, Hanny Pradany; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Digital transformation in public healthcare services is essential for efficiency and transparency. Specific background: RSUD Sidoarjo introduced the SANTRI application as an integrated hospital administration and queue system to streamline healthcare services. Knowledge gap: Despite its implementation, limited studies have comprehensively assessed its multidimensional role in improving service delivery. Aims: This study evaluates SANTRI based on program understanding, timeliness, target accuracy, tangible change, and goal achievement. Results: Findings reveal SANTRI accelerated administrative processes, reduced physical queues, integrated medical records, and improved patient satisfaction, though challenges persist in digital literacy, accessibility for vulnerable groups, and system optimization. Novelty: This study provides an in-depth evaluation of SANTRI within the framework of Sutrisno’s effectiveness theory, offering contextual evidence of digital service transformation in regional hospitals. Implications: The results underline the importance of strengthening digital literacy, accessibility, and system integration to sustain healthcare digitalization and present SANTRI as a replicable model for other hospitals in Indonesia. Highlights: SANTRI reduces queues and improves administrative efficiency. Accessibility challenges remain for elderly and digitally limited groups. Integration with SIMRS strengthens hospital service coordination. Keywords: SANTRI Application, Healthcare Digitalization, Queue System, Service Quality, RSUD Sidoarjo